DISCIPLINARY INSTITUTES, MINORITY LEGISLATION AND THE CONFIGURATION OF PUBLIC SECTORS SPECIALIZED IN THE ASSISTANCE OF MINORS IN SÃO PAULO (1900-1935) - Fonseca, Sérgio C. [UNESP]; Narita, Felipe Ziotti (Pontifical Catholic University of Sao Paulo (PUC-SP), 2019)
This article intends to analyze the formation of specialized sectors devoted to the management of public services of social assistance in São Paulo between the early 20th century and the 1930s. We emphasize the shift in reformatory institutions from their isolated condition to the rise of specialized structures of assistance. The research is based on legal documents and official reports. The differentiation within state dispositive is analyzed in light of the socioeconomic development as well as against the backdrop of institutional ramifications in health services, professionalization of the assistance and legal documents dealing with juridical and police procedures devoted to the management of population.
OS INSTITUTOS DISCIPLINARES, A LEGISLAÇÃO SOBRE MENORIDADE E A FORMAÇÃO DE SETORES ESTATAIS ESPECIALIZADOS EM ASSISTÊNCIA A MENORES EM SÃO PAULO (1900-1935)
Keywords: Frontier settlement; Reformatory; Social assistance